Порівняльний аналіз методів 3d-моделювання - Козловець, С. О.; Орлов, Д. І.; Рижкова, Є. М. (ХНУРЕ, 2024)
In this work, a comparative analysis of polygonal and voxel 3D modeling methods was carried out. The features of constructing models, disadvantages, and areas of application of these methods are considered. The basic elements of the models constructed by these methods, namely the polygon and the voxel, were studied.
Keywords: 3d-моделювання; 3D modeling